PENGARUH STRUKTUR MODAL SEBELUM DAN SESUDAH GO PUBLIC TERHADAP NILAI PERUSAHAAN - Patricia Kartika Surya (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
This research is aimed to distinguish the difference between the capital structure ofPT Sampoerna Agro Tbk before and after go public and also to find out whether the capital structure can affect the company’s value. This research utilizes “associative” and “comparative” methods which examines the relationship between two or more variables. Qualitative analysis is used to explore the relationship between variables using quantitative data derived fromPT Sampoerna Agro Tbk’s consolidated financial statements for the years ended December 31, 2004 to December 31, 2009. From the research results, the company’s capital structure affects the company’s value which is calculated by three test methods, which are Modigliani Miller Value (V), Enterprise Value Multiplier and Tobin Q, especially after go public